2009
DOI: 10.1155/2010/304315
|View full text |Cite
|
Sign up to set email alerts
|

Detection, Isolation and Characterization of Principal Synthetic Route Indicative Impurity in Lansoprazole

Abstract: An unknown impurity in lansoprazole (2-[[[3-methyl-4-(2, 2, 2-trifluoroethoxy)-2-pyridyl] methyl] sulfinyl] benzimidazole) was detected by HPLC and was identified as des-(trifluoroethoxy) lansoprazole, an principal synthetic route indicative impurity of lansoprazole. Lansoprazole was subjected to different ICH prescribed stress conditions like hydrolysis, oxidation, photolysis and thermal degradation conditions to enrich the impurity. The impurity was enriched by using acid catalytic degradation, isolated by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Earlier studies reported that lansoprazole was significantly more stable under basic and neutral hydrolyses than acidic hydrolysis or oxidation. Therefore, the forced degradation reactions were carried out at distinct incubation times with sampling performed at different time points; for more details refer to Table .…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies reported that lansoprazole was significantly more stable under basic and neutral hydrolyses than acidic hydrolysis or oxidation. Therefore, the forced degradation reactions were carried out at distinct incubation times with sampling performed at different time points; for more details refer to Table .…”
Section: Resultsmentioning
confidence: 99%
“…However, studies reporting the tautomeric populations of benzimidazoles have been overlooked, apparently due to the fast protropic exchange rate on benzimidazole nitrogens at room temperature [26]. Literature studies on benzimidazoles, almost exclusively, focused on synthetic methods and characterisation of benzimidazolyl derivatives [27,28,29]. Only a few researchers have discussed the tautomerism of benzimidazole compounds [24,30], and most studies were aimed at obtaining well-resolved NMR spectra instead of studying the structural tautomerism itself.…”
Section: Anticancer Potentialmentioning
confidence: 99%
“…The system suitability was established by evaluating the system suitability parameters from the chromatograms thus obtained. Typical system suitability parameters include %RSD, Tailing factor (T) and Theoretical plates (N) [12][13][14][15][16][17][18].…”
Section: System Suitabilitymentioning
confidence: 99%